Spectral editing of 13C cp/MAS NMR spectra of complex systems: application to the structural characterisation of cork cell walls. (Solid state nuclear magnetic resonance, 2000)
A mathematical method of obtaining 13C CP/MAS subspectra of single components of a complex system is presented and applied to three- and four-component systems. The method is based on previously reported work that exploits different proton relaxation properties for different domains of an heterogeneous system. However, unlike the original method that obtained subspectra through a trial-and-error approach, the method here presented solves the problem mathematically, thus avoiding the time-consuming and non-rigorous trial-and-error step. The method is applied to mixtures of three and four polymers and to a more complex system: cork cell walls. As expected, as the number of components increases, the sharing of relaxation properties between different components is increasingly probable, either due to incidental coincidence of relaxation times or to specific interactions and intimate mixing of compounds. While this hinders the calculation of the subspectra of single chemical components, it may provide useful information about inter-component interactions. This possibility was demonstrated by the application of this method to cork cell walls. Both three-component and four-component approaches showed that three domains exist in cork cell walls: carbohydrate/lignin matrix, mobile suberin close to (probably bonded to) lignin groups (about 42% w/w) and hindered suberin close to (probably bonded to) carbohydrate-OCH2O groups (about 4% w/w).